Pharmacological Considerations in Vaccination: Age-Specific Strategies for Pediatric and Geriatric Populations - Varsha S.Rathod; Dr.Sunil. K. Mahajan; Dr.Chandrashekhar D.Patil; Dipti B.Chavan; Gaurav M.Kasar (Asian Journal of Pharmaceutical Research and Development, 2026)
Vaccination remains one of the most effective public health strategies for preventing infectious diseases across the lifespan. However, age-specific immunological differences demand tailored pharmacological approaches in pediatric and geriatric populations. In children, immune immaturity, maternal antibody interference, and safety considerations necessitate fractional dosing, carefully timed booster schedules, and minimally reactogenic adjuvants. Combination vaccines and novel delivery systems, including microneedle patches and intranasal formulations, have further optimized pediatric immunization by reducing injection burden and improving acceptability. In contrast, older adults face immunosenescence, inflammaging, and the added burden of comorbidities, which collectively reduce vaccine responsiveness and durability. Pharmacological strategies in geriatrics emphasize dose intensification, potent adjuvants (MF59, AS01, Matrix-M), and next-generation platforms such as recombinant protein subunits and mRNA-based formulations. High-dose influenza vaccines, adjuvanted shingles vaccines, and recently licensed RSV and pneumococcal conjugate vaccines illustrate this paradigm. Age-related pharmacokinetic and pharmacodynamic differences also underscore the need for individualized approaches, as clearance, biodistribution, and immune priming vary significantly between neonates and older adults. Safety remains paramount, with febrile seizures in children and multimorbidity-linked adverse events in older adults requiring vigilant monitoring. Emerging innovations, including systems vaccinology, nanoparticle platforms, and thermostable vaccines, promise a future of personalized and lifelong immunization strategies. This review highlights the pharmacological basis for pediatric versus geriatric vaccine design, emphasizing that one-size-fits-all approaches are inadequate. Instead, age-tailored vaccine strategies informed by immune profiling, pharmacological principles, and regulatory frameworks are essential for optimizing protection across the lifespan.